PENGARUH MODEL PEMBELAJARAN INQUIRY TRAINING BERBANTUAN MEDIA PhET TERHADAP HASIL BELAJAR SISWA PADA MATERI FLUIDA STATIS KELAS X SEMESTER II SMA NEGERI 1 RAYA - Nababan, Evani Doana; Sirait, Makmur (JURNAL IKATAN ALUMNI FISIKA, 2016)
This research aims to determine the effect of inquiry training learning model using PhET simulation media to student learning outcomes on static fluid subject matter. This research is quasi-experimental design with two control group pretest-posttest. With random cluster sampling technique by taking two classes of seventh grade is class X MIA-1 as the experimental class and class X MIA-5 as the control class with each numbered 32 people. The research instruments used in the form of test results in cognitive learning form description consists of 8 questions that have been validated and observation sheet to assess the activities. The result showed an average value 34.9 pretest experimental class and control class pretest 33.1. After the treatment si given experimental class with inquiry training learning model using PhET simulation media dan control class with conventional learning the data obtained with the posttest average yield experimental class dan control class was 68,5 and 61,1. Development activity of experimental class gained an average categorized as very active, and control group gained an average growth of activity in the category of active. Based on the results of hypothesis testing using different test (t-test) obtained the influence of inquiry training learning model using PhET simulation media on student learning outcomes in a static fluid material in the second half of class X SMA Negeri 1 Raya.Â